Functional and structural evaluation in the lungs of children with repaired congenital diaphragmatic hernia - June-Young Koh; Euiseok Jung; Hyun Woo Goo; Seong-Chul Kim; Dae Yeon Kim; Jung-Man Namgoong; Byong Sop Lee; Ki-Soo Kim; Ellen Ai-Rhan Kim (BMC, 2021)
Abstract Background To evaluate the long-term functional and structural pulmonary development in children with repaired congenital diaphragmatic hernia (CDH) and to identify the associated perinatal-neonatal risk factors. Methods Children with repaired CDH through corrective surgery who were born at gestational age ≥ 35 weeks were included in this analysis. Those who were followed for at least 5 years were subjected to spirometry and chest computed tomography for evaluation of their functional and structural growth. Main bronchus diameters and lung volumes (total, left/right) were measured. According to total lung volume (TLV) relative to body surface area, children were grouped into TLV ≥ 50 group and TLV < 50 group and the associations with perinatal-neonatal factors were analyzed. Results Of the 28 children (mean age, 6.2 ± 0.2 years) with left-sided CDH, 7 (25%) had abnormal pulmonary function, of whom 6 (87%) showed restrictive patterns. All pulmonary functions except FEF25-75% were worse than those in matched healthy control group. Worse pulmonary function was significantly associated with small head and abdominal circumferences at birth. The mean TLV was 1339.1 ± 363.9 mL and LLV/TLV was 47.9 ± 2.5 mL. Children with abnormal pulmonary function were more likely to have smaller lung volumes. In multivariate analysis, abdominal circumference at birth was significantly associated with abnormal lung volume. Conclusions A quarter of children with repaired CDH showed abnormal pulmonary function. Small abdominal circumference at birth was associated with abnormal pulmonary function and lower TLV.